The Legal-International Statute of Jerusalem - Alfonso J. Iglesias Velasco (Revista CIDOB d'Afers Internacionals, 2000)
In the article, the author carries out a historical and juridical review of the main aspects of the controversy which the Jews and the Arabs confront regarding the sovereignty of the city of Jerusalem, considered sacred by their respective religions. In 1947, theUnited Nations General Assembly had designed a plan for the international and neutral administration of the city, but due to historical transformations and thanks to its victory in the Six Days War, Israel has had the exclusive administration of the city since 1967, with the intent to annex it to the Hebrew State, an issue which does not fail to spur a generalized rejection by the international community. In the framework of the Arab- Israeli peace process, the question of Jerusalem is still considered the most problematic and destabilizing issue in the agitated panorama of the Middle East.